COMMITMENT OF ACTORS IN DRUG PREVENTION COLLABORATION IN LHOKSEUMAWE CITY, INDONESIA - Aiyub; Endang Larasati; Sri Suwitri; Kismartini (RADJA PUBLIKA, 2023)
This research examines the commitment of actors in preventing drugs in Lhokseumawe City. This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, FGD and documentation. Qualitative data analysis through the stages of data collection, data presentation, data condensation and drawing conclusions that take place interactively. The results of the study show that the actors are committed to collaboration in drug prevention in realizing a Drug-Clean City in terms of the actors involved, the form of commitment and responsibility for the results of the collaboration, although there are still obstacles in terms of actors' budget support, coordination between actors and there is nomore binding cooperation agreements between actorsin the form of a Memorandum of Agreement (MoA).